Extracellular Vesicle-Loaded Oncogenic lncRNA NEAT1 from Adipose-Derived Mesenchymal Stem Cells Confers Gemcitabine Resistance in Pancreatic Cancer via miR-491-5p/Snail/SOCS3 Axis - Rongxiang Wu; Zhan Su; Le Zhao; Ruifeng Pei; Yiren Ding; Deqiang Li; Shuo Zhu; Lu Xu; Wei Zhao; Wuyuan Zhou (Stem Cells International)
It is becoming increasingly evident that key mechanisms of mesenchymal stem cell (MSC) efficacy appear to associate with paracrine activities, and the delivery of cargos through extracellular vesicles (EVs) controls the mechanistic actions of MSCs. Thus, this study clarified a possible mechanism by which EV-encapsulated NEAT1 from adipose-derived mesenchymal stem cells (ADSCs) might mediate gemcitabine resistance in pancreatic cancer (PCa). Microarray profile suggested a differentially expressed lncRNA NEAT1 in PCa, and we determined its expression in PCa cells. NEAT1 was found to be upregulated in PCa. The binding affinity among NEAT1, miR-491-5p, and Snail was identified through bioinformatic analysis and experimental validation. NEAT1 competitively bound to miR-491-5p to elevate Snail expression and diminish SOCS3 expression. PCa cells were cocultured with EVs extracted from ADSCs, followed by assessment of malignant phenotypes, tumorigenesis, and gemcitabine resistance of PCa cells using gain- or loss-of-function experiments. ADSC-derived EVs carrying NEAT1 promoted PCa cell proliferation, migration, and gemcitabine resistance in vitro and enhanced tumorigenicity in vivo by inhibiting miR-491-5p and SOCS3 and upregulating Snail. Collectively, the findings from our study found a new potential strategy for gemcitabine resistance in PCa by illustrating the mechanistic insights of oncogenic ADSC-derived EVs-loaded NEAT1 via regulating the miR-491-5p/Snail/SOCS3 axis.